Effect of Zn2+ and Nb5+ Co-doping on electrical properties of BCZT ceramics by the seed-induced method - Parjansri P. (2014)
The effects of Zn2+ and Nb5+ co-doping (x mol%ZN) on the electrical properties of lead-free Ba0.90Ca0.10Zr 0.10Ti0.90O3-Seed ceramic systems, where x = 0.0-1.0 mol% have been studied. The ceramics were prepared using the solid state reaction technique. The phase of the samples showed pure perovskite structure. The density values of the ceramics were in the range of 4.86-5.78 g/cm 3. The maximum dielectric constant was 40893 for 0.8 mol% ZN. The highest values of Pr ∼ 5.85 μC/cm2, d33 ∼ 381 pC/N and kp ∼ 38% were obtained for the sample of 0.4 mol% ZN. © 2014 Copyright Taylor and Francis Group, LLC.